Gender Parity in the Teaching of Science, Technology, Engineering, and Mathematics (Stem) in Cameroon - Nfon , Nekang, Fabian; Cheny , Nfor, Julius (Researchparks Publishing, 2024)
The paper discusses the gender disparity in education, particularly in Science, Technology, Engineering, and Mathematics (STEM). It examines the fact that teachers tend to stereotype mathematics as a male domain resulting in differential treatment of males and females in classrooms. This also results in the development of gender differences in STEM. It presents extracurricular, out of school factors and socio-cultural factors which contribute substantially to poor female enrolment in school thus causing serious gender imbalance in education in Cameroon and other African countries. The paper looks at the goals that lay the foundation for global policy on quality education and gender equity in the new millennium.